2018
DOI: 10.1111/iwj.12925
|View full text |Cite
|
Sign up to set email alerts
|

Bromelain‐based enzymatic debridement of chronic wounds: A preliminary report

Abstract: Sharp debridement is currently considered most effective for debridement of chronic wounds; however, some patients do not have access to or cannot be treated by surgical methods. This study was designed to provide a first impression of the safety and efficacy of bromelain-based enzymatic debridement of chronic wounds. Two consecutive single-arm studies assessing the enzymatic debridement efficacy of a concentrate of proteolytic enzymes enriched in bromelain in chronic wounds was conducted in 2 medical centres.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…Reports from preliminary clinical studies have indicate the potential safety and efficacy of bromelain-based enzymatic debridement in chronic wounds(6) and deep burn injuries (7). In addition, reports have shown that anti-inflammatory and analgesic characteristics of bromelain could be useful in the treatment of several chronic inflammatory disorders as osteoarthritis and rheumatoid arthritis (8–10).…”
Section: Introductionmentioning
confidence: 99%
“…Reports from preliminary clinical studies have indicate the potential safety and efficacy of bromelain-based enzymatic debridement in chronic wounds(6) and deep burn injuries (7). In addition, reports have shown that anti-inflammatory and analgesic characteristics of bromelain could be useful in the treatment of several chronic inflammatory disorders as osteoarthritis and rheumatoid arthritis (8–10).…”
Section: Introductionmentioning
confidence: 99%
“…[ 31c,33 ] Since, upon injury, the skin barrier is breached, it has been believed that the topical delivery of drugs would allow their proper penetration and distribution. However, the formed eschar, a crust of necrotic tissue that dries and hardens postinjury, [ 34 ] combined with exudate flow rich with various enzymes can lower the bioavailability of topically delivered compounds to the target cells. It has recently been shown that the intradermal delivery of therapeutics is superior to topically delivery for improving diabetic wound healing, [ 31c ] and there is growing interest in the use of MNAs to treat these kinds of wounds.…”
Section: Resultsmentioning
confidence: 99%
“…Wachstumsfaktoren die Wundheilung fördern sollen. Die Evidenz zu diesen Präparaten ist jedoch mäßig [13] (▶ Abb. 3).…”
Section: Enzymatische Wundheilungunclassified